Lightweight bricks made of diatomaceous earth, lime and gypsum - Pimraksa K. (2014)
Diatomaceous earth from Lampang Province in the north of Thailand composes of diatom, kaolinite, montmorillonite and illite, and has porous cellular structure. In this work, the diatomite, hydrated lime and gypsum are the main ingredients in making autoclaved lightweight bricks. Water content, pre-curing period, lime content, gypsum content and calcined temperature are the factors investigated. Mechanical and thermal properties are used to indicate their quality. The nature of hydration products and morphological characteristics of the lightweight bricks are also investigated. The results show that the diatomaceous earth possesses pozzolanic property and can be used for making lightweight bricks. The bricks made with untreated diatomite with 15% lime and 5% gypsum shows reasonably high strength of 14.5 MPa and low density of 0.88 g/cm3. Higher strength (17.5 MPa) and lower density (0.73 g/cm3) are obtained with the use of diatomite calcined at 500 °C. The incorporation of lime and gypsum with a Ca/Si ratio of 0.55, 50% water content and 6 days pre-curing results in formations of calcium silicate hydrate and gismondine which enhance strength development. Calcination of diatomaceous earth results in dehydroxylation of the clay minerals and contributes to additional pozzolanic reaction and better mechanical and thermal properties of the lightweight brick. © 2008 Elsevier Ltd and Techna Group S.r.l.